Wpływ zadrzewienia stref nadbrzeżnych na warunki termiczne niewielkich cieków nizinnych w okresie letnim - Łaszewski, Maksym; Kiryła, Wojciech (Leśne Prace Badawcze, 2018)
Riparian woodlands significantly affect the water quality of streams and rivers. Thus, we examined whether the presence of woodlands in riparian buffer zones also impacts the thermal characteristics of lowland streams during the summer. Water temperature data was recorded with digital temperature loggers located in eight quasi-natural sites across the Garwolin Plain in central Poland. The mean, maximum, minimum, and mean daily range parameters were calculated for the whole study period from July to September 2017 with 30 min. resolution. The contribution of woodlands in the catchment area and buffer zone along the streams was estimated based on satellite images from the Sentinel-1 and Sentinel-2 missions. The Random Forest method was used in the classification process with an accuracy of 96%. Similarity of measurement sites in terms of water temperature was determined using cluster analysis (Ward method), while a Spearman correlation coefficient was applied to link thermal parameters with the contribution of woodland areas. The results indicate that water temperature patterns across the measurement sites varied, with mean temperatures ranging from 14,4°C in site T8 to 16,3°C in site T1. Furthermore, the correlation analysis confirmed our hypothesis that the presence of woodland areas does not significantly alter the thermal parameters of lowland streams. Moreover, cluster analysis showed that sites with significantly different contributions of woodland areas were linked closely due to similar distributions of water temperature values. However, it must be emphasized that the lack of the riparian woodland in buffer zones does not exclude the presence of shade associated with shrubs and grasses, as well as aquatic plants. In consequence, more advanced indicators of riparian shade, such as vegetation mapping using UAV or hemispherical photography, should be employed for small lowland streams.